2006
DOI: 10.1111/j.1447-0578.2006.00126.x
|View full text |Cite
|
Sign up to set email alerts
|

Folliculogenesis following syngeneic transplantation of young murine ovaries into the testes

Abstract: To examine the effects of intratesticular transplantation on the growth and maturation of young murine ovaries. Two-week-old ovaries from transgenic mice with enhanced green fluorescent protein expression were transplanted under the testicular capsule of 4-week-old non-transgenic mice. Two months after transplantation all successfully grafted ovaries had survived, based on the presence of bright green fluorescence. The grafts showed various stages of folliculogenesis, including expanded follicles. The neighbor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…Similar results have been reported in rats, 29 rabbits 30 and sheep 31 . Furthermore, it has been reported that various stages of folliculogenesis were shown in young murine ovaries transplanted syngeneically into the testes 32 . Thus, the site of transplantation of ovarian tissues might be insignificant for the restoration of ovarian function after heterotopic ovarian transplantation.…”
Section: Discussionsupporting
confidence: 84%
“…Similar results have been reported in rats, 29 rabbits 30 and sheep 31 . Furthermore, it has been reported that various stages of folliculogenesis were shown in young murine ovaries transplanted syngeneically into the testes 32 . Thus, the site of transplantation of ovarian tissues might be insignificant for the restoration of ovarian function after heterotopic ovarian transplantation.…”
Section: Discussionsupporting
confidence: 84%
“…In this study, we improved the previously used method for intratesticular grafting of a juvenile ovary [12], and demonstrated that the grafted ovary still possesses the ability to ovulate oocytes when placed under a normal environment via ovary transplantation. Intratesticular grafting of an ovary was first performed by Sand [16,17], who found that the grafted ovary developed mature follicles, although the procedure remained unclear regarding the age of animal most suitable for obtaining donors and recipients and the most optimum stage of follicle maturation.…”
Section: Discussionmentioning
confidence: 95%
“…Improvement of testicular grafting of an ovary appears to be one of the factors leading to improved recovery of function in the ovaries grafted within the host testis. In our previous experiments [12], only about 40%-50% of STs were removed, which created a limited space, thus allowing the grafted ovary to grow normally. In this study, we removed about 80% of STs by suction by using 20-gauge needle, which gave rise to a larger space wherein the grafted juvenile ovary could grow well (Figure 2e).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations